Facilitating critical enquiry about race and racism in a digital environment: Design considerations - Brokensha, SI; Conradie, T (South African Journal of Higher Education, 2016)
Increasingly, instructors working in higher education settings are exploiting asynchronous online forums to facilitate difficult dialogues on social issues such as sexuality, race, and diversity. We interrogate the task design we employed to construct a digital space in which undergraduate English Studies students could discuss race and racism in the context of a study of contemporary understandings and manifestations of race. Within the realm of computer-mediated discourse analysis, we employed Booth and Hultén’s (2003)taxonomy of key contributions to meaningful online discussion to determine if students’ posts displayed not only knowledge-sharing discourse, but also knowledge-construction and knowledge-creation discourses. We discovered that although students co-constructed knowledge and, in some instances, created new artefacts, they mainly shared and compared ideas. We therefore consider how our task design should be altered to foster critical enquiry. Although not our main focus, we also take into account phenomena our data analysis revealed that cannot be overlooked when it comes to online discussions of contentious issues. These phenomena include emotional responses to racism and micro-aggressions. We adopt the view that these elements are an unavoidable part of a difficult dialogue, and that facilitators need to prepare their students to converse in uncomfortable spaces. Keywords: asynchronous online forums, difficult dialogues, task design, knowledge sharing, knowledge construction, knowledge creation